2007
DOI: 10.1371/journal.pone.0000220
|View full text |Cite
|
Sign up to set email alerts
|

A North American Yersinia pestis Draft Genome Sequence: SNPs and Phylogenetic Analysis

Abstract: Background Yersinia pestis, the causative agent of plague, is responsible for some of the greatest epidemic scourges of mankind. It is widespread in the western United States, although it has only been present there for just over 100 years. As a result, there has been very little time for diversity to accumulate in this region. Much of the diversity that has been detected among North American isolates is at loci that mutate too quickly to accurately reconstruct large-scale phylogenetic patterns. Slowly-evolvin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
27
0
1

Year Published

2009
2009
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(30 citation statements)
references
References 23 publications
2
27
0
1
Order By: Relevance
“…In addition, 14 unique SNPs were found. This parallels previous studies that have shown a range of two to 18 unique SNPs for each North American Y. pestis strain compared to CO92 (Auerbach et al 2007;Touchman et al 2007). Hopefully, with enhanced surveillance and molecular characterization of future isolates we can define Canadian-specific SNPs and contribute further to the understanding of the radiation of plague in Canada.…”
supporting
confidence: 89%
See 1 more Smart Citation
“…In addition, 14 unique SNPs were found. This parallels previous studies that have shown a range of two to 18 unique SNPs for each North American Y. pestis strain compared to CO92 (Auerbach et al 2007;Touchman et al 2007). Hopefully, with enhanced surveillance and molecular characterization of future isolates we can define Canadian-specific SNPs and contribute further to the understanding of the radiation of plague in Canada.…”
supporting
confidence: 89%
“…This included 14 unique SNPs (10 coding and four noncoding) not previously reported. The remaining 19 SNPs were previously reported between CO92 and other sequenced North American strains (Auerbach et al 2007;Touchman et al 2007). …”
mentioning
confidence: 99%
“…However, due to the genetically homogenous nature of the Y. pestis population, the application of these genotyping methodologies is, in many cases, beyond the resolution threshold and cannot resolve the individual phylogenetic relationships of distinct Y. pestis isolates. To resolve the population structure, we applied an SNPbased genotyping methodology using the modern 1.ORI strain CO92 as the reference genome (8,13,20,27,53,59,63). In this study, we identified for the species a total of 424 synonymous SNPs (sSNPs) and 1,006 nonsynonymous SNPs (nsSNPs) (see Table S3 in the supplemental material), which is far more than previously reported (1).…”
Section: Microevolution Of the Virulence Plasmidsmentioning
confidence: 99%
“…Single-nucleotide polymorphisms were identified in pairwise genome comparisons by comparing the predicted genes on the closed chromosome of Y. pestis strain CO92 to the completed genomes of strains KIM, Antiqua, Nepal516, 9001, and Pestoides F using MUMmer (19), and draft contigs were used for strains CA88-4125 (8) and FV-1 (63). By mapping the position of the SNP to the annotation in the reference strain CO92 genome, it was possible to determine the effect on the deduced polypeptide and classify each SNP as synonymous or nonsynonymous.…”
mentioning
confidence: 99%
“…All Y. pestis strains lacked or had a mutated yapX gene, highlighting a reductive evolutionary process that is typical for this species (39). Interestingly, all 13 North American strains of Y. pestis were biotype Orientalis strains and had lost yapV, even though the biotype Orientalis isolates from Asia and South America still carried yapV (43,44). The three African isolates also lacked yapV.…”
Section: Resultsmentioning
confidence: 95%